MINIMIZATION OF PHENOL AND AMMONIACAL NITROGEN IN REFINERY WASTEWATER EMPLOYING BIOLOGICAL TREATMENT - Silva, M.R.; Coelho, M.A.Z.; Araújo, O.Q.F. (Revista de Engenharia Térmica, 2002)
Wastewater from refineries is usually characterized by presence of phenol and ammoniacal nitrogen. The aim of this work was to search for a refinery wastewater minimization employing a biological technology to reduce these pollutants. Experimental data was obtained by treating a synthetic wastewater in a sequencing batch reactor (SBR) operating on different operational schemes for batch scheduling. COD, nitrate, ammonia, phosphate and phenol were monitored as well as dissolved oxygen, pH, level and redox potential through a supervisory control software. Reductions of 95 % were achieved for different concentrations of NH4 + and phenol, providing an effluent acceptable by Brazilian environmental legislation.